PENGEMBANGAN MEDIA POP-UP BOOK PADA SISWA KELAS V SD PADA MATERI KOMPONEN EKOSISTEM - William, Nanda; Vrianturi, Prastiwi; Kusumo Wardhani, Intan Susetyo (STAI Darul Kamal Darul Kamal NW Kembang Kerang, 2022)
Education is one of the needs that must be met in developing one's potential to have religious spiritual strength, self-control, personality, intelligence, noble character, and the skills needed by oneself, society, nation and country. However, based on the problems in the field, it is known that there is no learning media used in the learning process. The purpose of this research and development is to improve student learning outcomes through pop-up book media and to see the differences before and after the use of pop-up book media. The research method used in this research is Research and Development. The sampling technique used in this study used a purposive sampling technique. Data analysis in this study used a paired sample t-test with the help of SPSS 25.0 software. Based on the results of the study, there are differences in pop-up book media before and after the use of pop-up book media and there is an increase in student learning outcomes after using pop-up book media.